2016
DOI: 10.1007/s10811-016-1025-y
|View full text |Cite
|
Sign up to set email alerts
|

Is a cooperative approach to seaweed farming effectual? An analysis of the seaweed cluster project (SCP), Malaysia

Abstract: Seaweed (Kappaphycus spp.) farming has been practised in Malaysia since the late 1970s following government policy incentives (training and farming inputs). However, numerous governance, economic, environmental, technological and sociocultural challenges have limited the industry from achieving its full potential. The Seaweed Cluster Project (SCP) was introduced in 2012 to address some of these challenges. We sought to evaluate the effectiveness of the SCP in delivering its central objectives of increasing sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…In Malaysia, Sabah is the only state which produces seaweed at a commercial scale (26,076 tonnes in 2015) (Adibi et al 2016), and seaweed cultivation could potentially become one of the contributors to the country's income. Consequently, the Malaysian government has identified seaweed as one of the National Key Economic Areas (NKEA) under the Economic Transformation Programme (ETP).…”
Section: Research Context and Methodsmentioning
confidence: 99%
“…In Malaysia, Sabah is the only state which produces seaweed at a commercial scale (26,076 tonnes in 2015) (Adibi et al 2016), and seaweed cultivation could potentially become one of the contributors to the country's income. Consequently, the Malaysian government has identified seaweed as one of the National Key Economic Areas (NKEA) under the Economic Transformation Programme (ETP).…”
Section: Research Context and Methodsmentioning
confidence: 99%
“…systems for reportable/notifiable diseases and disease surveillance). Given the issues of miscommunication between national and regional governments, it is suggested that farmers may benefit from establishing groups (Nor et al 2017), or utilizing associations (e.g. Indonesian Seaweed Association ARLI or ASTRULI), so they can communicate and share the information regarding cultivation challenges and receive updates on innovations and related actions to mitigate for disease and pest outbreaks (Neish 2013;Neish et al 2017).…”
Section: National Biosecurity Componentsmentioning
confidence: 99%
“…Indonesian Seaweed Association ARLI or ASTRULI), so they can communicate and share the information regarding cultivation challenges and receive updates on innovations and related actions to mitigate for disease and pest outbreaks (Neish 2013;Neish et al 2017). In 2014, the World Wildlife Fund (WWF) took proactive action and published better management practices (BMP) together collaborated with local seaweed farmers in promoting sustainable fisheries and responsible aquaculture for supporting the SNI initiative (Nor et al 2017). Collaborations between academia, government and industry to share information are also crucial to building biosecurity capacity amongst the Indonesian seaweed community.…”
Section: National Biosecurity Componentsmentioning
confidence: 99%
“…This provided resources for the Seaweed Cluster Project (SCP) initiated in 2012 by the Sabah Fisheries Department and the Mini-Estate programme. An excellent evaluation of the SCP was published by Nor et al (2016). The SCP was given the mandate to increase seaweed production, optimize farming area, improve seaweed quality and farming efficiency, while enhancing income of farmers, and reducing the environmental impact of seaweed farming (Nor et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An excellent evaluation of the SCP was published by Nor et al (2016). The SCP was given the mandate to increase seaweed production, optimize farming area, improve seaweed quality and farming efficiency, while enhancing income of farmers, and reducing the environmental impact of seaweed farming (Nor et al, 2016). The evaluation exercise carried out by Mr. Adibi M. Nor showed that the "SCP outcomes were generally negative".…”
Section: Introductionmentioning
confidence: 99%